The Effect of Tui Na Acupressure on Appetite in Children (Toddlers) Aged 1-3 Years at the Wulandari Purba Clinic, Batang Quiz in 2022 - Saddiyah Rangkuti (Institute of Computer Science (IOCS), 2022)
Symptoms of decreased appetite found in childhood are worth 25%, this rate increases to 40-70% in children. Decreased hunger can often be felt by children, especially at the age of 1-3 years, the problem of eating difficulties that continues to occur causes problems in the development and growth of children. The purpose of this study was to determine the effect of tui na acupressure on increasing appetite in children aged 1-3 years at the Wulandari Purba Clinic in 2022. The type of research conducted was quantitative. Pre-experimental design with the One Group pre-test and post-test design approach without a control group, the population in the study was 50 people using the accidental sampling technique of 25 people. The data collected in this study is primary data, namely data obtained from direct respondents. The data analysis used was univariate analysis and bivariate analysis. The results of the Preacupressure tui na study on increased appetite in children aged 1-3 years, namely the majority experienced less appetite as many as 14 (56%) respondents. Post acupressure tui na on increased appetite in children aged 1-3 years, namely the majority have a good appetite as many as 18 (72%) respondents. There is an Effect of Tui Na Acupressure on Increasing Appetite in Children Aged 1-3 Years. The conclusion from this study is that there is an effect of Tui Na acupressure on increasing appetite in children aged 1-3 years